EFEKTIVITAS PIJAT OKSITOSIN TERHADAP PRODUKSI ASI: EFFECTIVENESS OF oxytocin massage on breast milk production - Hanum, Sri Mukhodim Faridah; Purwanti, Yanik; Khumairoh, Ike Rohmah (Jurnal Kebidanan Midwiferia, 2015)
Breastfeeding is beneficial to maintain the resilience of the baby's body because it contains anti-infective agents. It is expected that all mothers can deliver their babies exclusively breastfed, but when when the control day 7, 50% of mothers had brought a bottle with formula milk for babies. Therefore, intensive efforts are needed to help new mothers breastfeed their babies normal order, one of them with oxytocin massage can help breast milk production.The purpose of this study was to examine the effectiveness of massage oxytocin on milk production in mothers postpartum normal.This research method uses Quasy design experiments with quasi-experimental research design or the non-randomized design without posttest control group design. Sampling with purposive sampling. Samples of 40 people normal postpartum mothers who were divided into 2 groups, ie 20 massage respondents 20 respondents without oxytocin and oxytocin massage.The results showed the average age of mothers 20-35 years (92.5%), multiparous (70%). Based on the results of statistical analysis with the chi-square test showed that t value 9.22> t table 3.84 thus Ho is rejected and H1 is accepted.Conclusion The majority of milk production in postpartum mothers is quite normal and there is a difference between postpartum maternal milk production after getting a massage and oxytocin. Massage oxytocin is one way to facilitate and increase milk production. Massage oxytocin is one example of an independent midwife and interventions easily been in treatment stimulates milk production.